1986
DOI: 10.1103/physrevlett.57.507
|View full text |Cite
|
Sign up to set email alerts
|

Energy Dependence of Spin Effects inp+pp+p

Abstract: We measured the analyzing power A and the spin-spin correlation parameter A nn , in large-Pi proton-proton elastic scattering, using a polarized-proton target and the polarized-proton beam at the Brookhaven Alternating-Gradient Synchrotron. We also used our polarimeter to measure A at small P] at 13 GeV with good precision and found some deviation from the expected 1/P| ab behavior. At 18.5 GQV/C we found A m = ( -2 ± 16)% at P\ =4.7 (GeV/c) 2 . Comparison with lower-energy data from the Argonne Zero-Gradient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…The results show an increase of T with incident momentum up to about 10 GeV/c but it drops at higher momenta. This result as well as the anomalous spin asymmetry observed in pp scattering at similar center of mass energies [25] have been interpreted [26] as the contribution from a resonance produced by a higher Fock state. The authors predict that CT will reappear at higher energies.…”
Section: Quasi-elastic Scatteringmentioning
confidence: 60%
See 1 more Smart Citation
“…The results show an increase of T with incident momentum up to about 10 GeV/c but it drops at higher momenta. This result as well as the anomalous spin asymmetry observed in pp scattering at similar center of mass energies [25] have been interpreted [26] as the contribution from a resonance produced by a higher Fock state. The authors predict that CT will reappear at higher energies.…”
Section: Quasi-elastic Scatteringmentioning
confidence: 60%
“…scattering angle θ cm = 60 • in the interval of the deuteron beam energy 0.5−1.2 GeV and ∼s −16 for d p → d p scattering at θ cm = 125 • -135 • at beam energies 0.5-5 GeV [24]. The anomalous spin asymmetry in pp scattering [25] has been interpreted [26] as the contribution from a higher Fock state: |uuduudcc that couples to the J = S = 1 initial state thus affecting the spin asymmetry. The electromagnetic moments of the deuteron have been calculated in the LCWF framework [27].…”
Section: Nuclear Effectsmentioning
confidence: 99%
“…Examples of nuclear-bound quarkonium are the |uuduudss > and |uuduudcc > resonances which apparently appear as intermediate states in pp → pp elastic exchange. These resonances can account [20] for the large spin-spin A N N correlations [21] observed at the strangeness E cm 3 GeV and E cm 5 GeV and charm thresholds.…”
Section: Production Of Exotic Atoms In Flight and Hadronization Amentioning
confidence: 86%
“…Brodsky and de Teramond [37] suggested that the oscillations and also the associated large values of the A NN spin correlations observed in pp scattering [39] …”
Section: Oscillations With Energymentioning
confidence: 99%